Perceived Transformational Leadership and Instructional Efficacy among Teachers in a Selected School in Manila - Villanueva, Ricardo; Cuayzon, Mark Lester (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between perceived transformational leadership and instructional efficacy among classroom teachers in a selected school in DepEd Manila and served as the basis for a comprehensive supervisory plan. It was anchored on Transformational Leadership Theory, Social Cognitive Theory, and Distributed Leadership Theory, which collectively explain how leadership behaviors influence teacher confidence, professional growth, and instructional practice. Using a quantitative correlational-descriptive design, the study gathered data from 106 purposively selected teachers out of a population of 165 during the school year 2025–2026. A structured survey questionnaire adapted from established teacher efficacy and transformational leadership scales was validated, pilot-tested, and administered through Google Forms. Data were analyzed using frequency, percentage, mean, standard deviation, Pearson r, and multiple regression. Findings showed that the respondents were predominantly early-career teachers, many of whom were already pursuing graduate studies. Head teachers were perceived to demonstrate a very high level of transformational leadership, with Idealized Influence receiving the highest rating, while classroom teachers likewise reported a very high level of instructional efficacy, especially in instructional strategies. A strong positive and statistically significant relationship was found between transformational leadership and instructional efficacy. Regression analysis further revealed that Intellectual Stimulation and Idealized Influence were the strongest positive predictors of instructional efficacy, while student engagement remained the most challenging area for teachers. The study concluded that transformational leadership significantly enhances teachers’ instructional efficacy and that leadership practices must combine inspiration with intellectual challenge and practical support. It recommended the integration of transformational leadership into supervisory plans, leadership training, and professional learning interventions. The study aligns with SDG 4, SDG 8, and SDG 17 by supporting quality education, professional development, and collaborative institutional improvement. Its sustainability impact lies in strengthening educational and institutional sustainability through improved leadership, teacher development, and long-term school effectiveness.